Thermodynamic properties and glass transition temperature of roasted and unroasted carob (Ceratonia siliqua L.) powder. (1st December 2019) - Červenka, Libor; Stępień, Anna; Frühbauerová, Michaela; Velichová, Helena; Witczak, Mariusz
Highlights: GAB isotherms successfully described the experimental moisture content data. Strongly bound water molecules in unroasted carob powder were observed. Different integral thermodynamic properties were determined. Roasted carob powder exhibited better stability.